Hair follicle response to the variable l.e.t. of a helium ion beam - Molinari de Rey, Beatriz L.; Bernaola, Omar Alberto; Mazzei, R.; Suquet, G. (Taylor & Francis Ltd., 1986)
Fil: Molinari de Rey, Beatriz L. Comisión Nacional de Energía Atómica; Argentina